Gonadal steroids levels and vitellogenesis in the formation of oocytes in Prochilodus lineatus (Valenciennes) (Teleostei: Characiformes) - Hainfellner, Patrick [UNESP]; de Souza, Thiago Gonçalves [UNESP]; Moreira, Renata Guimarães; Nakaghi, Laura Satiko Okada [UNESP]; Batlouni, Sergio Ricardo [UNESP] (FapUNIFESP (SciELO), 2012)
The objective of this study was to obtain information about the possible mechanisms related to poor reproductive performance in tropical rheophilic fish. To that effect, cages (Cs) and earthen ponds (EPs) were used as experimental systems to provide unsuitable and suitable conditions, respectively, for curimbatá (Prochilodus lineatus) breeders. Fish were maintained under experimental conditions for 18 months, and during this period females were randomly sampled every two months for biometric analysis (n=30), blood (n=5/sampling) and ovary (n=5/sampling). After this period EPs females (EPFs) and Cs females (CFs) were submitted to the induced breeding experiments. The results showed that rearing curimbatá for such long time in a cage at this stocking density, reduces its growth, plasma E2 levels and vitellogenesis. During vitellogenesis, the mean plasma estradiol levels of CFs were three times lower than those of EPFs (P<0.01). CFs presented poorer results than EPFs for all the examined parameters of reproductive performance. Taken together these data showed that the reduced estradiol levels during vitellogenesis (and the consequently less intense transition from the previtellogenic to vitellogenic phase) and reduced amounts of yolk are mechanisms associated with the formation of low quality oocytes and shortened and delayed breeding season in this species. Moreover, our data showed that the onset of vitellogenesis (six months before the spawning season) must be considered as a key period related to the formation of oocytes of good quality, and adequate management should be provided throughout the year. © 2012 Sociedade Brasileira de Ictiologia.
Keywords: Reproductive cycle; Spawning performance; Steroid levels; Tropical rheophilic fish